2018
DOI: 10.12659/msm.907853
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride Inhibits Proliferation of Ovarian Cancer Cells via Phosphatidylinositol 3-Kinase (PI3K) Signaling Pathway

Abstract: BackgroundOvarian cancer is the second most common malignant tumor of the female reproductive system and is the leading cause of death of gynecological malignancies, but at present there is no effective and safe therapy. There is no previously published report on the anti-cancer effect of prucalopride, which is a high-affinity 5-HT4 receptor. The aim of the present study was to determine whether prucalopride can inhibit proliferation of ovarian cancer cells.Material/MethodsThe cell viability was detected by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Other work revealed that autophagy was stimulated following the phosphorylation of AKT, the activation of mTor phosphorylation, and the repression of p70S6K, while prucalopride was suggested to hinder the initial step. 11,30 Consistent with this, we found that the inhibition of the PI3K/AKT/mTor signaling pathway contributed to autophagy. Specifically, we observed that the downregulation of p-AKT and p-mTor was accompanied by Beclin 1 reduction and the conversion of LC3.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other work revealed that autophagy was stimulated following the phosphorylation of AKT, the activation of mTor phosphorylation, and the repression of p70S6K, while prucalopride was suggested to hinder the initial step. 11,30 Consistent with this, we found that the inhibition of the PI3K/AKT/mTor signaling pathway contributed to autophagy. Specifically, we observed that the downregulation of p-AKT and p-mTor was accompanied by Beclin 1 reduction and the conversion of LC3.…”
Section: Discussionsupporting
confidence: 84%
“…10 Liu et al confirmed that prucalopride can inhibit cell behaviors in ovarian cancer. 11 However, it is unknown whether prucalopride could be used to treat lung cancer. Therefore, this study attempted to investigate the antitumor activity of prucalopride in lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic cells were detected according to a previously described method. 15 Briefly, SH-SY5Y cells (5×10 5 cells/ well) were seeded to 6-well plates overnight, then treated with BUP (500 μM) and/or TET (200 μM), or BUP+TET +3MA. Cell scraper was used to detach the cells from the culture plate.…”
Section: Flow Cytometric Analysis Of Cell Apoptosismentioning
confidence: 99%